The energy expenditure and relative excercise intensity of Pound ® - Ryskey, Abigail (My University, 2017)
Purpose: To determine the energy expenditure and relative exercise intensity during a Pound® cardio jam session. Methods: Six male (age 22.8 ± 1.72 years) and 16 female (age 20.8 ± 2.17 years) subjects performed a graded exercise test on a treadmill. Then subject performed a 38-minute Pound® cardio-jam session. Heart rate and VO2 were monitored every minute throughout the workout and perceived exertion was recorded approximately every 4 minutes throughout the session using the Borg 6-20 RPE scale. Results: It was found that both %HRMax (males: 68 ± 5.2; females: 73 ± 6.8) and % VO2max (males: 39 ± 4.5; females: 42 ± 6.6) met ACSM guidelines for improving cardiorespiratory endurance. Throughout the workout subject considered the workout to be of "somewhat hard" intensity on the 6-20 Borg RPE scale (Average RPE = 12.7 ± 1.91). Energy expenditure for both males (280.8 ± 41.38 kcal/session) and females (221.8 ± 34.35 kcal/session) also met ASCM guidelines for weight loss. Males had a significantly higher energy expenditure than females due to higher body mass (165 ± 19.77 lbs vs. 149.5 ± 15.98 lbs). Conclusion: The Pound® cardio jam session meets the standards set forth by ACSM to improve cardiorespiratory fitness and weight composition.
Keywords: Physical fitness; Cardiopulmonary system; Physical education and training